Potencial de uso agrícola de levedura seca inativa de cana-de-açúcar e de resíduos orgânicos - Braga, Marilena de Melo [UNESP] (2014)
The use of organic waste as fertilizer may cause improvement in chemical and physical soil properties, as these residues have significant amounts of nutrients, especially N, and high organic carbon content. In general, the availability of these C residues to the ground is smaller as compared with synthetic fertilizers, because of the way that N is connected to these fertilizers. Therefore, there is the necessity studies in order to estimate the mineralization of N and the time these reactions occur, assisting a suitable recommendation of this waste as fertilizer. Thus, the aim of this work was to evaluate (I) under laboratory conditions, inactive dry yeast mineralization of sugarcane (ULCI), chicken manure (EG), cattle manure in corral confinement (EB) and biosolids (BS) in soil and (II) under field conditions, yeast efficiency compared with mineral fertilizers in maize, therefore, two experiments were conducted. The first was conducted in controlled laboratory conditions in a completely randomized design in a 5 x 3 x 2 factorial, with three replications and 10 sampling periods. Therefore, experimental units 900 were installed to allow destructive sampling at the end of each period. The treatments consisted of four organic waste (EB, EG, ULCI and BS) and control (soil), three levels of soil moisture (15, 45 and 85% of maximum soil water holding capacity) and two conditions soil acidity improvement (uncorrected and corrected to reach a saturation basis of 70%). The kinetics of N release from the different nitrogen sources were determined by measuring ammonium and nitrate content periodically over 16 weeks. The organic N mineralization of waste fractions (FNmin) increased in the order: LISC (18-80%)> EG (27-70%)> EC (12-51%)> LE (5-26%). The increase of soil moisture improved the N mineralization in both limed soils as well as in the uncorrected for all wastes. The soil correction provided greater mineralization and nitrification in ...